HUBUNGAN PEMBERIAN KONSUMSI PROTEIN HEWANI DENGAN PERTAMBAHAN BERAT BADAN PADA BALITA GIZI KURANG DI DESA TIMBANG KECAMATAN CIGANDANEKAR KABUPATEN KUNINGAN TAHUN 2023 - Muhamad Ikhsan Prawira Negara; Alfiani Rizki; Faisal Azhar Sugandi (Universitas Islam Al-Ihya Kuningan, 2023)
The purpose of this study was to determine the consumption of animal protein and weight gain, and to find out how big the relationship between animal protein consumption and weight gain in malnourished toddlers aged 24-59 months in Timbang Village, Cigandamekar District, Kuningan Regency in 2023. This research using analytic observational (non-experimental) with a Cross Sectional approach. The subjects of this study were malnourished toddlers in Timbang Village, Cigandamekar District, with a total of 48 toddlers. The instrument used is a questionnaire. The results of the study regarding the relationship between animal protein consumption and body weight gain, there is a significant relationship between animal protein consumption and weight gain for undernourished toddlers in Timbang Village, Cigandamekar District in 2023 with a value of ρ = 0.013 (ρ value <0.05).